monólogo de humor Un proyecto de educación literaria - Rodríguez Suescun, Nora (Huarte de San Juan. Filología y Didáctica de la Lengua, 2013)
The aim of this article is to show a proposal for literary education focused on the «stand-up» comedy, framed in the drama genre and the «spectacular paradigm ». In these pages, I suggest a teaching sequence whose final output is writing and dramatizing a monologue individually. The main objective is to approach literature to students by providing them successful experiences and to work with humor as a transverse element for educational mediation. Moreover, a reflection about the essence of drama by the students is intended and the development of their creativity and linguistic expression, plastic and artistic body is expected as well.